Some Notes on the Reception of Josquin and of Northern Idioms in Portuguese Music and Culture - Alvarenga, João Pedro d' (2014)
Although Josquin is by far the best-represented foreign composer in Gonçalo de Baena's Arte novamente inventada pera aprender a tanger (Lisbon, 1540), his music is undeniably under-represented both in the extant sixteenth-century Portuguese manuscripts containing Franco-Flemish polyphony and in volumes imported from the Netherlands such as Coimbra MM 2 and VienNB 1783. Josquin’s reputation made him, along with Ockeghem, a symbol in Portuguese humanistic culture, but up to at least the late 1530s his name seems to have been much better known than his music. Nevertheless, possible allusions to specific works by Josquin can be found in early- and mid-sixteenth-century Portuguese polyphony. By the 1520s, the general technical and stylistic characteristics of his and the following generation of northerners had begun to permeate locally produced polyphony. This eventually replaced the late-fifteenth- and early-sixteenth-century pan-consonant and homorythmic style associated with the Aragonese and the so-called Spanish court repertory.